PENGELOLAAN HARTA BAITUL MAL DAN KEMASLAHATAN UMAT: KAJIAN MASA PEMERINTAHAN KHULAFAUR RASYIDIN - Shafwan Bendadeh; Mohammad Haikal (STISNU Aceh, 2023)
This study discusses the management of Baitul Mal asset and the benefit of the people. Baitul Mal is an institution that carries out the economic and social functions of an Islamic state that cannot be separated from the function of the caliph who has a special task of managing all the assets of the people, both in the form of income and expenses for the state. This study will discuss how the management of Baitul Mal funds during the Khulafaur Rasyidin era. This research is a library research using a descriptive method approach. By getting data from primary sources, namely texts or books that will provide an overview of the management of baitul mal funds during the reign of Khulafaur Rasyidin. The results of this study are; a) Caliph Abu Bakr Ash-Siddiq applies the concept or principle of Balance Budget Policy (equality) in the matter of living necessities and policies on Baitul Mal assets that have been collected are not allowed to accumulate in the long term, must be immediately distributed to all Muslims; b) When Umar bin Khattab became caliph, the wealth or cash owned by the state in Baitul Mal increased very significantly. Umar succeeded in expanding his territory, establishing al-Diwan, appointing a clerk for the state, setting salaries for government employees, as well as making and budgeting budgets for the armed forces in order to strengthen national defense; c) At the time of Caliph Uthman bin Affan, the wealth of the state was increasing compared to the previous caliph. Ustman also applied the principle of equality in meeting the basic needs of the community as was applied by Caliph Umar. Caliph Ustman also provided different assistance at a higher level; and d) Caliph Ali bin Abi Talib in terms of the distribution of assets applies the principle of equity. In addition, all state income stored in the Baitul Mal must be immediately given to the Muslims without any remaining or reserve funds.